2005
DOI: 10.1038/sj.bmt.1705101
|View full text |Cite
|
Sign up to set email alerts
|

What would Karl Landsteiner do? The ABO blood group and stem cell transplantation

Abstract: Summary:ABO blood group antigens, of great importance in transplantation and transfusion, are present on virtually all cells, as well as in soluble form in plasma and body fluids. Naturally occurring plasma IgM and IgG antibodies against these antigens are ubiquitous. Nonetheless, the ABO blood group system is widely ignored by many transfusion services, except for purposes of red cell transfusion. We implemented a policy of transfusing only ABO identical platelets and red cells in patients undergoing stem cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 65 publications
4
21
0
Order By: Relevance
“…(Cells were purified and cultured as described previously.) 3,4 We observed that Teriflunomide induced a decrease of viable cells in a dose-dependent manner. Importantly, a dose of 10 mM Teriflunomide was sufficient to decrease cell proliferation compared to DSP30/IL-2-stimulated cells in the absence of the inhibitor (P ¼ 1.36 Â 10 À7 , Figure 1a).…”
Section: Test (Categorical Variables)mentioning
confidence: 73%
See 1 more Smart Citation
“…(Cells were purified and cultured as described previously.) 3,4 We observed that Teriflunomide induced a decrease of viable cells in a dose-dependent manner. Importantly, a dose of 10 mM Teriflunomide was sufficient to decrease cell proliferation compared to DSP30/IL-2-stimulated cells in the absence of the inhibitor (P ¼ 1.36 Â 10 À7 , Figure 1a).…”
Section: Test (Categorical Variables)mentioning
confidence: 73%
“…One reason is that ABO mismatching of donor and recipient has little effect on clinical outcome in allogeneic stem cell transplantation. 4 We hypothesized that immune function may be important in eradicating residual disease during and after induction therapy in acute leukemia and that transfusion might alter immune function. We examined retrospectively the survival in adult patients with acute leukemia who systematically participated in different protocols for transfusion including ABO identical versus nonidentical platelets, leukoreduced versus non-leukoreduced transfusions and washed versus unwashed transfusions.…”
Section: S Galimbertimentioning
confidence: 99%
“…132 One group described favorable results of transfusing only ABO-identical red cells and platelet products for patients undergoing autologous or allogeneic transplantation, claiming improved survivals compared with results published by other transplant programs. 133 A retrospective study of pediatric patients found a correlation between ABO-incompatible plasma infusions and hepatic sinusoidal syndrome, possibly a consequence of expression of ABO antigens in the liver. 134 Multivariate analysis found only two factors that predicted for this event, use of melphalan in the pre-transplant conditioning (P ¼ 0.006) and transfusion of platelet concentrates containing ABO-incompatible plasma (P ¼ 0.003).…”
Section: Transfusion Support For Red Cell-incompatible Transplantationmentioning
confidence: 99%
“…This low incidence of refractoriness is likely due to our protocol that from 1990 onward mandated transfusion of only leukoreduced, ABO identical platelets for all patients at high risk of platelet transfusion refractoriness. 4,79 …”
Section: Methodsmentioning
confidence: 99%
“…4 For example, AB plasma, long considered the universal donor plasma, and thought to be compatible with all recipients, contains both A and B soluble antigens. When AB plasma is transfused to an O, A or B type recipient possessing anti-A and/or anti-B antibodies, antibody-antigen interactions occur and may be clinically significant in the case of type O recipients, including an association with a 9% increase in mortality.…”
Section: Introductionmentioning
confidence: 99%